Protective Effects of Baicalin on Decidua Cells of LPS-Induced Mice Abortion - Xiaodan Wang; Yantao Zhao; Xiuhui Zhong (Journal of Immunology Research)
The study was carried out to investigate the protective effects of Baicalin on decidual cells of LPS-induced abortion mice. In the in vitro experiment, the decidual cells were cultured by uterus tissue mass cultivation sampled at day 6 of pregnancy, and gradient concentrations of LPS were used to determine the optimal LPS concentration of the injured decidual cells model. The injured decidual cells were treated with Baicalin (4 μg/mL) to determine the protective role of Baicalin. In the in vivo experiment, lipopolysaccharide (LPS) was injected intravenously via the tail vein to induce abortion at day 6 of pregnancy, and the mice were given different concentrations of Baicalin by oral gavage consecutively at days 7 to 8 of pregnancy. On day 9 of gestation, the mice were sacrificed. The TNF and progesterone contents in the serum were assayed by ELISA. The results clearly revealed that Baicalin can prevent the injury to decidual cells from LPS dose dependently, TNF was decreased significantly (P<0.01) compared to LPS group, and there was no effect on the progesterone. These findings suggest that Baicalin has protective effects on the injured decidual cells in the pregnant mice.